ANALISIS TANDA DALAM FILM THE DAVINCI CODE KARYA DAN BROWN - LAJA, AGNES NOVITA SARI PUTRI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Â This study is entitled â€œAnalisis Tanda Dalam Film The DaVinci Code Karya Dan Brown: Analisis Semiotikâ€. Semiotics is a study about signs. Sign is something that can be interpreted. Every sign has various meaning according to the convention that exist in society. This study is an attempt to identify and classify the sign and then to analyze the meaning of the sign that appears in The DaVinci Code Film. This research was done in several stages: preparation, data collection and data analysis. The data were collected through the authorâ€™s explaination about kind of signs as something that have meanings. The writer used the theory of Pierce to identify, classify andÂ  analyze the the data.Â  Â The results of this research show that there are three kinds of signs that appear in The DaVinci Code Film. Those are icon, index and symbol. The meanings of the signs are various toward the context of each scene. The writer hopes that this study will help the readers to understand about semiotics especially on sign that often found in our daily lives and how these signs can giveÂ  meaning in communication. Â  Keywords: Signs, Semiotic Analysis, Film